The Road to CAR T-Cell Therapies for Pediatric CNS Tumors: Obstacles and New Avenues - Burns, Ian; Gwynne, William D.; Suk, Yujin; Custers, Stefan; Chaudhry, Iqra; Venugopal, Chitra; Singh, Sheila K. (Frontiers in Oncology, 2022)
Pediatric central nervous system (CNS) tumors are the most common solid tumors diagnosed in children and are the leading cause of pediatric cancer-related death. Those who do survive are faced with the long-term adverse effects of the current standard of care treatments of chemotherapy, radiation, and surgery. There is a pressing need for novel therapeutic strategies to treat pediatric CNS tumors more effectively while reducing toxicity – one of these novel modalities is chimeric antigen receptor (CAR) T-cell therapy. Currently approved for use in several hematological malignancies, there is promising pre-clinical and early clinical data that suggests CAR T-cells could transform the treatment of pediatric CNS tumors. There are, however, several challenges that must be overcome to develop safe and effective CAR T-cell therapies for CNS tumors. Herein, we detail these challenges, focusing on those unique to pediatric patients including antigen selection, tumor immunogenicity and toxicity. We also discuss our perspective on future avenues for CAR T therapies and potential combinatorial treatment approaches.